Governance and cooperation in Euroregions: border tourism between Spain and Portugal - Liberato, Dália (2018)
There are several obstacles to establish tourism governance policies in a border area and to improve the conceptualization of tourism in border territories transcending the transnational level, using territorial delimitation at Euroregional level. At borders, tourism usually works as a strategic policy tool to strengthen the regional image, shape common identity narratives and facilitate interactions, becoming these regions, nowadays, challenges for the actors of the territory, representing a priority area for the application of territorial development strategies at local level and at the level of the European Union itself. A qualitative analysis was based on performed semistructured interviews with key tourism stakeholders. From the intervieweeś perspective, cooperation should be achieved through cooperation agreements between the business sector and economic agents to develop natural, cultural and heritage resources.